THE PROBLEMATIC OF FOREIGN ACCENT UNDER THE PRISM OF DAR MULTILINGUA-MULTIPERSONALIA: LEARNING THROUGH HEALING AS A WAY TO FULL CULTURAL IMMERSION AND SUCCESSFUL SOCIETAL INTEGRATION - Kupriianova, Larysa; Kupriianova, Daryna (Collection of scientific papers «ΛΌГOΣ», 2023)
Nowadays there are various attitudes towards the accent while speaking foreign languages, that are supposed to be analyzed under the prism of the process of ensuring a proper integration and social inclusion in migrants/refugees and forcibly displaced persons. Some educational institutions, mentors, tutors, teachers and ordinary people claim:“it is completely enough to be comprehensible”, therefore, consequently, it does not matter “whether you do literally sound as a local/native or not”. At the same time, multiple old-fashioned attitudes to learning disclose age limits, until which the individual can or cannot learn a given language. To add, there are ordinary personal limitations, prejudices, biases, fears, doubts on the matter of a new linguistic experience, which make the person “blocked inside his/her personal fears”. Moreover, though, while we are taking into consideration particularly refugees and forcibly displaced persons, therefore, ones, who are being displaced as a result of e.g. war, armed conflicts, riot, political and/or economical instabilities etc., there are extraordinary limitations that enter the stage of a research. The reality though requires modern and “appropriate attitudes to a process of a language learning”, in the aim of not becoming an “infinite foreigner” and, as a result, not to be totally separated from the successful social inclusion and integration and, subsequently, from an opportunity to apply a personal potential in full. DAR Multilingua is becoming a remedy for the aforementioned state of affairs and advises successful solutions for all potential problems in the learning process. The specific attitude to learning, under the prism of a unique method that we have mentioned above, is being analyzed in the current research.